(untitled) (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2025)
The low level of student creativity in history learning remains a persistent challenge in secondary schools. As a core 21st-century skill, creativity supports critical thinking, self-expression, and problemsolving, yet history learning is still dominated by memorization and teacher-centered instruction. This research employed Classroom Action Research (CAR) using John Elliot’s model, consisting of problem identification, planning, action implementation, monitoring, and reflection. The intervention was conducted by integrating project-based digital storytelling into the learning process. The findings show a significant increase in four creativity indicators: fluency, flexibility, originality, and elaboration. The average creativity score increased by 8.5 points, from 22.6 in Cycle I to 31.1 in Cycle II, while the percentage of creativity rose from 58% to 80% (22% increase). These results confirm that project-based digital storytelling is an effective pedagogical strategy for fostering student creativity in history education. The study offers a replicable instructional model that integrates digital media and project-based learning, shifting history education from traditional rote learning toward participatory and creative practices. Theoretically, it contributes to the discourse on creative pedagogy and digital integration in history education; practically, it provides teachers with an innovative model to optimize digital technology in the classroom.